LOOKING AT THE POTENTIAL OF PERSONNEL IN THE HOSPITALITY INDUSTRY AS THE BASIS OF THE COMPANY'S COMPETITIVENESS - Shermamatova Nilufar (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: The article discusses the essential ways of importance of the market of tourism and hotel services in Samarkand. It directs the role of human resources in the activities of hotels. And it looked through the effect of quality management on the resource potential of the enterprises of hotel industry. The particularity of hospitality industries in Samarkand is that, although most the officials consider tourism & hospitality a strategic priority, a vast majority of researchers and industrialists agree that not enough steps have been done. Our research concentrated to the case of Samarkand, a region facing the challenge of limited qualified employees in the field, and was built upon qualitative and quantitative tools, examining three groups of potential, part-time & full-time employees, as well as employers, as a fourth group.